Combining law with medical ethics. - Greaves, D (1987)
A postgraduate Diploma in Medical Ethics and Law was started in October 1984 by the Centre of Medical Law and Ethics at King's College. It is a part-time one year course designed so as to enable students to continue with full-time employment if they wish. It is multidiscipinary and is open to all who have a first degree in a relevant discipline, for example law, philosophy, theology, medicine and nursing studies. It is unique in combining medical law and medical ethics and has attracted students of high calibre from a variety of backgrounds during its first three years. Building on the experience of the diploma the course is being upgraded to an MA in 1987-88. It will be available either full-time for one year or part-time for two years.